The Dynamics of Territorial Boundary Conflict between Bedengung and Nyelanding Villages in Southern Bangka Regency - Bung Apitrianto; Bahjatul Murtasidin; Sandy Pratama (JURNAL KUASA, 2025)
This study examines the conflict dynamics and resolution efforts at the boundary between Bedengung Village and Nyelanding Village in South Bangka triggered by the construction of a palm oil mill in the border area of the two villages in 2023. This conflict demonstrates the complexity of the relationship between village governments in managing resources of directly adjacent areas, especially in the context of economic development that affects the interests of the people in both villages. This study aims to determine the efforts taken by the village government in resolving boundary conflicts to realize a fair and sustainable resolution for all parties involved. Galtung conflict triangle theory is used as a conceptual framework to look the dynamics of the conflict, as well as the resolution approach applied. The methodology used is descriptive qualitative, with data collection techniques through in-depth interviews, field observations, and analysis of relevant documentation. The results of research showed that there is CSR interest in the boundary conflict between Bedengung Village and Nyelanding Village. There are attitudes in the conflict including elite, community, offensive and defensive attitudes. Destructive behavior in the conflict is manifested in debates and riots during mediation at the Regional Secretariat of South Bangka. There are contradiction due to CSR interests and the unclear boundaries between Bedengung Village and Nyelanding Village. The settlement efforts, through a peacebuilding approach at the deliberation held on April 22, 2024, successfully reached an agreement as stated in the Memorandum of Understanding (MoU) and approved by all parties involved.